THE ROLE OF HOSPITAL IN OVERALL HEALTH DELIVERY SYSTEM - M. Nozadi (Tehran University of Medical Sciences, 1982)
Since hospitals are an important and integral part of the overall health delivery system, this study was carried out to measure the effectiveness of this institution within the system. The records of 633 hospitalized patients in the pediatrics ward of Ghaem Hospital in Mashhad during 1357 (21 March 1978-20 March 1979) has been consulted. More than half of the patients were hospitalized with the following diagnoses: Bronchopneumonia, Gastroentritis, Septicemia, and Malnutrition. Bronchopneumonia peaked in winter, whereas Gastroentritis and Malnutrition peaked in summer. Most of the hospitalized patients were male and the malnutrition was limited to the pre-school children of 1-6 years of age. The importance of these findings in development and utilization of the health delivery system has been discussed and considering the preventable nature of the above mentioned diseases, development and expansion of primary health care activities has been stressed.